2013
DOI: 10.1127/0003-5548/2013/0363
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination by three-dimensional geometric morphometrics of the palate and cranial base

Abstract: The purpose of this study is to assess sexual dimorphism in the palate and base of adult crania using three-dimensional geometric morphometric methods. The study sample consisted of 176 crania of known sex (94 males, 82 females) belonging to individuals who lived during the 20th century in Greece. The three-dimensional co-ordinates of 30 ectocranial landmarks were digitized using a MicroScribe 3DX contact digitizer. Generalized Procrustes Analysis (GPA) was used to obtain size and shape variables for statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 57 publications
2
21
0
2
Order By: Relevance
“…Taking into account the general morphometric features, male palates analysed in this study were longer, broader and deeper than the female ones, which generally complies with the findings of other authors [5]. However there are works showing that it is the female palate that is actually wider and longer [3].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Taking into account the general morphometric features, male palates analysed in this study were longer, broader and deeper than the female ones, which generally complies with the findings of other authors [5]. However there are works showing that it is the female palate that is actually wider and longer [3].…”
Section: Discussionsupporting
confidence: 76%
“…Though much has been written on traditional and novel (geometric morphometrics) approaches to sexing human bones, the palatine bones themselves received little attention [3,5,8]. Recent years have brought about an increase of interest in palatal measurements in forensic medicine, mainly due to the introduction of geometric morphometrics [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…The centroid size was included as a DV because many earlier studies have found it to differ significantly between males and females (Chovalopoulou et al, ; Franklin et al, ; Nikita, ). Centroid size is computed as the total Euclidean distance of the coordinates of the bregma, nasion, opisthocranion, and superior‐most point on external auditory meatus from their centroid (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have adopted metric approaches for estimation of sex using the cranium (e.g., Brasili, Toselli, & Facchini, ; Caple & Stephan, ; Kranioti, İşcan, & Michalodimitrakis, ), while more generalized use of geometric morphometric techniques has facilitated studies that focus on capturing the overall morphology of the cranium or of specific cranial structures (e.g., Bigoni, Velemínská, & Brůžek, ; Chovalopoulou et al, ; Nikita, ). Among those focusing on the morphology of specific cranial structures using geometric morphometry, Garvin and Ruff () explored sexual dimorphism in the supraorbital ridges and mental eminence of US males and females.…”
Section: Introductionmentioning
confidence: 99%
“…A study was done in 176 adult Greek crania, in which the classification accuracy was 82% and 79% for size and shape, respectively, and on cross validation, the classification accuracy was 77.2% [20]. The classification accuracy can be improved when both size and shape were used in combination (90.4% for cranial base), as shown in a study on 106 South African White crania and 90 South African Black crania, in which 13 standard cranial parameters were measured, and the results showed that the classification had yielded from 86.7% up to 97.8% for males, and yielded from 81.1% to 95.8% for females [21].…”
Section: Discussionmentioning
confidence: 99%